Simultaneous combined anterior and posterior approach for en bloc resection of sciatic notch sarcomas - Elodie Gaignard; Dimitri Tzanis; Toufik Bouhadiba; David C. Kieser; Fabien Robin; Damien Bergeat; Bernard Meunier; Sylvie Bonvalot (BMC Surgery, 2019)
Abstract Background Monobloc resection of soft tissue sarcomas (STSs) has a major impact on overall survival and local recurrence. Anatomical boundaries, such as the sciatic notch, increase the risk of fragmentation of the lesion. To date there are few papers describing the optimal surgical technique to remove such STSs. The objective of this study is to describe a simultaneous anterior and posterior approach for resection of sciatic notch dumbbell tumours. Case presentation We present the surgical management of two patients diagnosed with well-differentiated liposarcomas of the sciatic notch with a retroperitoneal and gluteal extension in the two cases. Pre-operative diagnosis was made with a percutaneous biopsy including molecular analysis which demonstrated MDM2 amplification. We describe a simultaneous anterior and posterior approach, including the ligation of the posterior trunk of the internal iliac artery, to reduce intra-operative blood loss and devascularise the tumour. The anterior approach allows the evaluation of the tumour’s retroperitoneal extension, release from its pelvic attachments and control of the surrounding neurovascular structures. During the posterior approach, bleeding is reduced by the devascularisation of the gluteal musculature achieved with internal iliac artery ligation. Clear margins were achieved in both cases. No vascular, skeletal or soft tissue reconstructions were required. Conclusions Simultaneous combined anterior and posterior approaches to remove a malignant sciatic notch tumour optimises the chance of complete en bloc resection. This surgical strategy allows oncologic en bloc resection with minimal blood loss.